Penentuan Komoditas Pangan Unggulan Di Kabupaten Nganjuk - Farah, Regina; Mubarokah, Mubarokah; Sari Tondang, Ika (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2025)
This research aims to analyze the superior food commodities in Nganjuk Regency. The results of this study are expected to be able to become a reference in regional economic development through the priority development of superior food crop commodities in Nganjuk Regency. The data used in this study are secondary data including data on the value of food commodity production for 10 years starting from 2014-2023. The food commodities studied include rice, corn, soybeans, peanuts, cassava, shallots, and cayenne pepper. The data analysis methods used are Location Quotient and Shift Share Analysis, the results of the two analyses will be combined into criteria for determining superior food commodities. The results of this study indicate that corn, shallots, and cayenne pepper are the first and second superior commodities in several districts in Nganjuk Regency. Rice, soybeans, peanuts, and cassava became the second and third superior commodities in several sub-districts in Nganjuk Regency.